Assessing the interaction between depressive symptoms and alcohol use prior to antiretroviral therapy on viral suppression among people living with HIV in Rural Uganda. Issue 10 (2nd October 2020) - Foley, Jacklyn D.; Sheinfil, Alan; Woolf-King, Sarah E.; Fatch, Robin; Emenyonu, Nneka I.; Muyindike, Winnie R.; Kekibiina, Allen; Ngabirano, Christine; Samet, Jeffrey H.; Cheng, Debbie M.; Hahn, Judith A.
ABSTRACT: Although there is evidence of individual associations between depressive symptoms and hazardous alcohol use with suboptimal antiretroviral therapy (ART) adherence among people living with HIV (PLWH), few studies have established how the two risk factors may interact to predict viral suppression. We conducted secondary data analyses with two cohorts of Ugandan PLWH ( N = 657) to investigate the hypothesized interaction between depressive symptoms (Center for Epidemiological Studies Depression Scale) and hazardous alcohol use (Alcohol Use Disorder Identification Test -Consumption and/or Phosphatidylethanol biomarker) prior to ART initiation with viral suppression (<550 copies/ml). We were unable to detect an interaction between depressive symptoms and hazardous alcohol use prior to ART initiation with viral suppression in the first two years ( M = 19.9 months) after ART initiation ( p = 0.75). There was also no evidence of a main effect association for depressive symptoms (Adjusted Odds Ratio [AOR] = 0.88, 95% Confidence Interval [CI]: 0.50, 1.55) or hazardous alcohol use (AOR = 1.37, 95% CI: 0.80, 2.33). PLWH with depressive symptoms and/or hazardous alcohol use appear to exhibit similar levels of viral suppression as others in care; further work is needed to determine effects on HIV testing and treatment engagement.